Expiratory obstruction in patients with Duchenne muscular dystrophy under non-invasive ventilation: A step-by-step analysis of a new obstructive pattern. (28th August 2021) - Léotard, Antoine; Delorme, Mathieu; Delord, Vincent; Niel-Duriez, Myriam; Orlikowski, David; Annane, Djillali; Prigent, Hélène; Lofaso, Frédéric
Purpose: Non-invasive ventilation (NIV) is the reference standard for managing chronic hypoventilation in patients with Duchenne muscular dystrophy (DMD). In these patients, upper airway obstruction under NIV may compromise efficacy and adherence. We aim to describe a novel pattern of expiratory obstructive events occurring during nocturnal barometric NIV. Methods: We retrospectively included all patients with DMD who underwent full-night polygraphy during NIV as part of their usual follow-up between May 2018 and July 2019. Results: We provide a step-by-step description of this previously undescribed pattern of obstruction. Expiratory obstructions lead to end-inspiratory breath-holding and impossibility to take another inspiratory breath with a barometric mode until expiration occurs. These events were observed in 4 (36%) of 11 DMD patients under barometric NIV. Conclusion: Expiratory obstructions may be common in DMD patients receiving NIV and should be sought out routinely. This previously undescribed variant of obstructive event must be identified.